Catalytic article comprising ammoxidation catalyst
By introducing porous coating structures of precious metals and molecular sieves into the catalyst, the problem of insufficient ammonia conversion at low temperatures of the existing AMOx catalyst is solved, and more efficient ammonia oxidation and reducing ammonia escape are achieved.
Patent Information
- Application Number
- CN202380056172.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-07-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing AMOx catalysts have insufficient conversion rate of escaped ammonia at low temperatures, resulting in ammonia escaping poses a threat to the environment and health.
A catalytic article with a porous coating structure containing noble metal catalysts and molecular sieve catalysts is used to improve ammonia oxidation efficiency by forming a coating with high porosity on the substrate.
Under low temperature conditions, the conversion rate of ammonia is significantly improved, the ammonia escape is reduced, and the environmental friendliness and safety of the catalyst is improved.
Smart Images

Figure BDA0005256224240000241
Abstract
Description
Technical Field
[0001] The present invention relates to selective ammonia oxidation (AMO) x ) catalysts, methods for making the same, and catalyst systems for treating exhaust gas flows. Background Art
[0002] Diesel engine exhaust is a heterogeneous mixture that contains particulate emissions such as soot and gaseous emissions, including carbon monoxide (CO), unburned or partially burned hydrocarbons (HC), and nitrogen oxides (collectively referred to as NOx). Catalyst compositions (usually arranged on one or more monolithic substrates) are placed in the engine exhaust treatment system to convert some or all of these exhaust components into harmless compounds. Due to the adverse environmental effects of NOx on ecosystems, humans, animals and plants, the control of NOx emissions has always been one of the most important topics in exhaust treatment, especially for diesel engines.
[0003] Various treatment methods, such as catalytic reduction of nitrogen oxides, have been used to reduce NOx in exhaust gas. A typical catalytic reduction method is selective catalytic reduction using ammonia (NH3) or an ammonia precursor as a reducing agent in the presence of atmospheric oxygen, which is also called the SCR method. The SCR method is considered to be superior because a high degree of NOx reduction can be obtained with a small amount of reducing agent. Generally, nitrogen oxides and the reducing agent NH3 react according to the following equation:
[0004] 4NO+4NH3+O2→4N2+6H2O (standard SCR reaction)
[0005] 2NO2+4NH3+O2→3N2+6H2O (slow SCR reaction)
[0006] NO+NO2+2NH3→2N2+3H2O (fast SCR reaction).
[0007] In the SCR method, a stoichiometric excess of the reducing agent ammonia or its precursor is usually metered into the exhaust flow to reduce NOx at the highest possible conversion rate. Excess ammonia can leave the exhaust pipe of the car. Another potential scenario in which ammonia can leave the exhaust pipe is when the operating temperature rises, a large amount of ammonia is desorbed from the SCR catalyst, which has been retained on the Lewis and Bronsted acid sites on the surface of the SCR catalyst during the low temperature part of the typical driving cycle. If ammonia is released into the air (also known as ammonia slip), many problems will arise. Ammonia slip is harmful to human health and the environment. It is known that ammonia may cause significant eye and throat irritation above 100 ppm, significant skin irritation above 400 ppm, and the IDLH value of ammonia in air is 500 ppm. In addition, ammonia is caustic, especially in its aqueous solution form. Condensation of ammonia and water in the cooler area of the exhaust line downstream of the exhaust catalyst will produce a corrosive mixture, thereby damaging the exhaust line. Ammonia should be eliminated before entering the tail pipe.
[0008] An ammonia oxidation (AMOx) catalyst (also called an ammonia slip catalyst (ASC)) installed downstream of the SCR catalyst is usually used to convert the slipped ammonia into N2. Such catalysts are known and usually contain a precious metal active material for oxidizing ammonia and usually also a SCR active material.
[0009] WO 2010 / 062730A2 describes a catalyst system for treating an exhaust gas flow containing NOx, the system comprising at least one integral catalyst substrate; an undercoat carrier coating, which is coated on one end of the integral substrate and contains a material composition A that effectively catalyzes the oxidation of NH3; and an outer coating carrier coating, which is coated on the integral substrate over a length sufficient to cover at least a portion of the undercoat carrier coating and contains a material composition B that effectively catalyzes the selective catalytic reduction (SCR) of NOx, which material composition may contain a zeolite or a non-zeolite molecular sieve.
[0010] WO 2017 / 037006A1 describes a catalyst for the oxidation of ammonia, the catalyst comprising a carrier coating, the carrier coating comprising copper or iron on a small pore molecular sieve material, the small pore molecular sieve material having a maximum ring size of eight tetrahedral atoms physically mixed with platinum or platinum and rhodium on a refractory metal oxide carrier. In this patent application, a partitioned catalyst for the oxidation of ammonia is also described, the partitioned catalyst comprising a first carrier coating zone, the first carrier coating zone comprising copper or iron on a small pore molecular sieve material having a maximum ring size of eight tetrahedral atoms, the first carrier coating zone being substantially free of platinum group metals; and a second carrier coating zone, the second carrier coating zone comprising copper or iron on a small pore molecular sieve material, the small pore molecular sieve material having a maximum ring size of eight tetrahedral atoms physically mixed with platinum on a refractory metal oxide carrier (including alumina, silica, zirconia, titania, and physical mixtures or chemical combinations thereof, including atomic doping combinations).
[0011] WO 2020 / 210295A1 describes a catalyst comprising an AMOx catalyst and an SCR catalyst, wherein the SCR catalyst is located in a region upstream of the AMOx catalyst, in a layer above the AMOx catalyst, or uniformly blended with the AMOx catalyst, or any combination thereof. The AMOx catalyst contains a platinum group metal on a support, and the SCR catalyst contains a zeolite or non-zeolitic molecular sieve and optionally a promoter metal.
[0012] US 2021 / 0299643A1 describes a catalytic article comprising a substrate having an inlet and an outlet, a first coating comprising a blend of (1) platinum on a carrier and (2) a first SCR catalyst, and a second coating comprising a second SCR catalyst, wherein the carrier comprises at least one of a molecular sieve or a SiO2-Al2O3 mixed oxide, and wherein the first SCR catalyst comprises a Cu and Mn exchanged molecular sieve.
[0013] The excellent catalytic performance of the AMOx catalyst in terms of NH3 conversion at low temperatures (particularly about 250°C) is important because the exhaust gas temperature will be reduced to this temperature when it reaches the AMOx catalyst after passing through upstream exhaust treatment components (such as one or more of the diesel oxidation catalyst (DOC), filter and SCR catalyst).
[0014] It would be desirable if the AMOx catalyst had improved catalytic performance for converting escaped ammonia to N 2 at low temperatures. Summary of the invention
[0015] It is an object of the present invention to provide a catalytic article comprising an SCR catalyst and a precious metal-based catalyst that can perform better than conventional AMOx catalytic articles for converting escaped ammonia at low temperatures, in particular at about 250°C.
[0016] This object is achieved by a catalytic article comprising a porous coating comprising a molecular sieve component on a substrate.
[0017] Thus, in a first aspect, the present invention relates to a catalytic article for treating an exhaust gas stream, the catalytic article comprising
[0018] - substrate,
[0019] - a coating comprising a first catalyst comprising a noble metal component and a second catalyst comprising a molecular sieve component,
[0020] In the first coating structure;
[0021] or
[0022] - substrate,
[0023] - a first coating comprising a first catalyst comprising a precious metal component, and
[0024] - a second coating covering at least a portion of the first coating and comprising a second catalyst comprising a molecular sieve component,
[0025] In the second coating structure;
[0026] The coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 5.7% or more.
[0027] In a second aspect, the present invention relates to a method for preparing a catalytic article for treating an exhaust gas stream, the method comprising
[0028] - applying a slurry comprising a first catalyst comprising a precious metal component, a second catalyst comprising a molecular sieve component, and a pore former to a substrate, optionally drying, and calcining to form a coating in a first coating structure,
[0029] or
[0030] - A first slurry comprising a first catalyst containing a precious metal component is applied to a substrate and dried and / or calcined to form a first coating, and then a second slurry comprising a second catalyst containing a molecular sieve component and a pore former is applied, optionally dried, and calcined to form a second coating in a second coating structure, wherein the pore former is in particulate form and is used in an amount of at least 15% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0031] In a third aspect, the present invention relates to a system for treating an exhaust gas flow, the system comprising a reductant source (e.g., NH3 or a precursor thereof), a catalytic article as described herein, and optionally one or more of a diesel oxidation catalyst (DOC), a selective catalytic reduction catalyst (SCR), a three-way conversion catalyst (TWC), a four-way conversion catalyst (FWC), a non-catalyzed or catalyzed soot filter (CSF), a NOx trap, a hydrocarbon trap catalyst, a sensor, and a mixer.
[0032] In a fourth aspect, the invention relates to a method for treating an exhaust gas stream containing nitrogen oxides, the method comprising contacting the exhaust gas stream with a catalytic article as described herein or passing the exhaust gas stream through a system as described herein in the presence of NH3 as a reducing agent.
[0033] The inventors have surprisingly discovered that an AMOx catalytic article having a porous coating containing a molecular sieve component according to the present invention can provide improved NH3 conversion at low temperatures, particularly about 250°C, compared to an AMOx catalytic article without a porous coating as described herein. DETAILED DESCRIPTION
[0034] The present invention will be described in detail hereinafter. It should be understood that the present invention can be implemented in many different ways and should not be construed as limited to the embodiments set forth herein.
[0035] As used herein, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise. The terms "comprise", "comprising", and the like are used interchangeably with "contain", "containing", and the like and are to be interpreted in a non-limiting, open-ended manner. That is, for example, additional components or elements may be present. The expression "consisting of" or "consisting essentially of" or cognates may be included in "comprise" or cognates.
[0036] Herein, the term "inter-particle pores" refers to pores formed during the preparation of the coating, including voids created by stacking of starting material particles and voids left by burning off pore formers, which does not include intra-particle pores inherent in the starting material particles.
[0037] In this document, any reference to "upstream" and "downstream" should be understood as relative positions with respect to the direction of exhaust gas flow (eg, the flow direction of the exhaust gas flow).
[0038] As used herein, the term "coating" refers to a covering deposited on the surface of the wall of the substrate, the wall of the substrate defining a channel for the exhaust gas flow to pass through. The coating can consist of a single coating or of two or more coatings. It should be understood that the coating can be prepared by repeating the coating step two or more times to obtain a target loading and will therefore contain more than one sublayer with the same chemical composition and catalytic activity. Such a coating containing more than one sublayer with the same chemical composition and catalytic activity will be referred to as a coating.
[0039] As used herein, the term "porosity" in the context of a coating means the ratio of the total cross-sectional area of pores in a cross-sectional surface perpendicular to the axial direction of the substrate (i.e., the exhaust gas flow channel direction) to the total cross-sectional area of the coating, as measured by SEM.
[0040] As used herein, the term "solid content" is intended to refer to the content of matter that is not volatile under calcination conditions, expressed as a weight ratio measured before and after the calcination process (eg, at 500°C for 1 hour).
[0041] According to a first aspect, the present invention provides a catalytic article for treating an exhaust gas stream, the catalytic article comprising
[0042] - substrate,
[0043] - a coating comprising a first catalyst comprising a noble metal component and a second catalyst comprising a molecular sieve component,
[0044] In the first coating structure;
[0045] or
[0046] - substrate,
[0047] - a first coating comprising a first catalyst comprising a precious metal component, and
[0048] - a second coating covering at least a portion of the first coating and comprising a second catalyst comprising a molecular sieve component,
[0049] In the second coating structure;
[0050] The coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 5.7% or more.
[0051] In some specific embodiments, the catalytic article for treating an exhaust gas stream according to the present invention comprises
[0052] or
[0053] - substrate,
[0054] - a first coating comprising a first catalyst comprising a precious metal component, and
[0055] - a second coating covering at least a portion of the first coating and comprising a second catalyst comprising a molecular sieve component,
[0056] The second coating layer has inter-particle pores with a porosity of 5.7% or more.
[0057] <Base Material>
[0058] Substrates useful in catalytic articles according to the present invention generally refer to structures suitable for withstanding conditions encountered in exhaust gas streams, carrying thereon catalytic materials in the form of a coating (usually a washcoat). The substrate may have an inlet end and an outlet end defining its axial length and a plurality of thin parallel gas flow channels extending along the axial length.
[0059] The substrate is usually inert and conventionally made of, for example, ceramic or metallic materials, which are also referred to as “inert substrates.” The substrate may alternatively be active and may consist, for example, of extrudates containing catalytically active substances.
[0060] The substrate can be a monolithic flow-through structure having a plurality of thin parallel gas flow channels extending from the inlet end of the substrate to the outlet end, so that the channel is open to the fluid passing therethrough. The channel (which is a substantially straight path from its fluid inlet to its fluid outlet) is defined by a wall, on which a catalytic material is applied as one or more coatings (e.g., a carrier coating) so that the gas flowing through the channel contacts the catalytic material. The flow channels of the monolithic substrate are thin-walled channels, which can have any suitable cross-sectional shape and size, such as a trapezoid, rectangle, square, sinusoid, hexagon, ellipse, circle, etc. Such structures can contain 60 to 900 or more flow channels (or "units") per square inch of cross section. For example, the substrate can have 60 to 700 units per square inch ("cpsi"). The wall thickness of the flow-through substrate can vary, with a typical range of 2 mils to 0.1 inches.
[0061] The substrate can also be a monolithic wall-flow structure with a plurality of thin parallel gas flow channels extending along the inlet end of the substrate to the outlet end, wherein the alternating channels are blocked at the opposite end. The channel is defined by a wall, and a catalytic material is applied on the wall as one or more coatings (e.g., a carrier coating) so that the gas flowing through the channel contacts the catalytic material. The structure requires the gas to flow through the porous walls of the wall-flow substrate to reach the outlet end. The wall-flow substrate can have up to 700 cpsi, for example, 100 to 400 cpsi. The flow channels of the monolithic substrate are thin-walled channels, which can have any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. The wall thickness of the wall-flow substrate can vary, with a typical range of 2 mils to 0.1 inches.
[0062] The term "washcoat" has its ordinary meaning in the art and refers to a thin, adherent coating of catalytic or other material applied to a substrate. Washcoats are typically formed by preparing a slurry containing the desired materials and optional processing aids such as a binder having a certain solids content (e.g., 15% to 60% by weight), and then applying the slurry to the substrate, drying and calcining to provide a washcoat. Washcoats in the form of one or more layers are typically applied in an amount of 0.1 to 10 g / in 3 , for example 0.3 to 7 g / in 3 , or 0.5 to 4 g / in 3 The amount is loaded on the substrate.
[0063] <First Catalyst>
[0064] The first catalyst may be a noble metal-based oxidation catalyst commonly used to catalyze the conversion of NH3 to form N2, which typically comprises a noble metal component, preferably a platinum group metal component. The noble metal component may contain one or more selected from ruthenium, rhodium, iridium, palladium, platinum, silver and gold on the particles of the carrier. Preferably, the noble metal component contains one or more selected from ruthenium, rhodium, iridium, palladium and platinum on the particles of the carrier, more preferably palladium and platinum, and most preferably platinum.
[0065] In some embodiments, the precious metal component is substantially free of any platinum group metals (PGMs) other than Pt, and particularly substantially free of any precious metals other than Pt.
[0066] In this article, the term "substantially free" in the context of precious metal components is intended to mean that no PGM or precious metal other than Pt is intentionally added or used. It should be understood by those skilled in the art that trace impurity PGM or precious metal from the raw materials may be unavoidable. Trace amounts generally refer to amounts less than 1% by weight, including less than 0.75% by weight, less than 0.5% by weight, less than 0.25% by weight, or less than 0.1% by weight.
[0067] It should be understood that the noble metal may be present in any possible valence state, for example as the corresponding metal or metal oxide in a catalytically active form, or may be, for example, a corresponding metal compound, complex, etc., which decomposes or is otherwise converted to a catalytically active form upon calcination or use of the catalyst.
[0068] Useful materials as supports for the precious metal in the first catalyst can be any material suitable for receiving and supporting the precious metal, such as molecular sieves, oxides of metals selected from the group consisting of: Ti, Si, W, Al, Ce, Zr, Mg, Ca, Ba, Y, La, Pr, Nb, Mo, Mn, Fe, Co, Ni, Cu, Zn, Ga, Sn, Sm, Eu, Hf and Bi.
[0069] In particular, the support for the noble metal may be selected from high surface area aluminas (e.g., having a surface area of 50 to 300 m 2 / g specific surface area of ?-alumina), silica, titania, ceria, zirconia, lanthanum oxide, barium oxide, yttrium oxide, neodymium oxide, praseodymium oxide, titania, europium oxide, samarium oxide, hafnium oxide, and any composite material or combination thereof. Exemplary supports may be composite oxides of silica-alumina, alumina-zirconia, alumina-lanthanum oxide, alumina-chromium oxide, alumina-barium oxide, or alumina-ceria.
[0070] It should be understood that two or more precious metal components (if present) may be supported on the same or different support particles; and that the same precious metal component may be supported on one or more types of support particles.
[0071] <Second Catalyst>
[0072] The second catalyst comprises a molecular sieve component, which can be a zeolite or non-zeolitic molecular sieve with selective catalytic reduction (SCR) activity. The molecular sieve component that can be used for the second catalyst is optionally metal-promoted. In this article, molecular sieve refers to a framework material based on a wide three-dimensional network of oxygen ions, which generally contains tetrahedral sites and has a substantially uniform pore distribution. Suitable molecular sieves for the purpose of the present invention can be microporous or mesoporous.
[0073] In particular, the molecular sieve component may be an optionally metal-promoted zeolite.Herein, the term "metal-promoted" in the context of molecular sieves is intended to mean that a metal capable of improving any property of the zeolite has been incorporated into and / or onto the zeolite.
[0074] Preferably, suitable molecular sieves may include, but are not limited to, aluminosilicate zeolites having a framework type selected from the group consisting of AEI, AEL, AFI, AFT, AFO, AFX, AFR, ATO, BEA, CHA, DDR, EAB, EMT, ERI, EUO, FAU, FER, GME, HEU, JSR, KFI, LEV, LTA, LTL, LTN, MAZ, MEL, MFI, MOR, MOZ, MSO, MTW, MWW, OFF, RTH, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TON, TSC and WEN. More preferably, the molecular sieve comprises a zeolite having a framework type selected from the group consisting of AEI, BEA (e.g., β), CHA (e.g., chabazite, SSZ-13), AFT, AFX, FAU (e.g., zeolite Y), MOR, MFI (e.g., ZSM-5), MOR (e.g., mordenite), and MEL, with CHA and AEI being particularly preferred.
[0075] It should be understood that when zeolites are referred to herein by reference to framework type codes such as those generally accepted by the International Zeolite Association (IZA), it is intended to include not only the reference material, but also any isotype framework material having SCR catalytic activity. A list of reference materials and isotype framework materials for each framework type code can be obtained from the IZA database (http: / / www.iza-structure.org / databases / ).
[0076] In some embodiments, the molecular sieve component in the second catalyst can be a metal-promoted zeolite selected from those described above. The promoter metal can be selected from precious metals such as Au and Ag, platinum group metals such as Ru, Rh, Pd, In and Pt, base metals such as Cr, Zr, Nb, Mo, Fe, Mn, W, V, Al, Ti, Co, Ni, Cu, Zn, Sb, Sn and Bi, alkaline earth metals such as Ca and Mg, and any combination thereof. The promoter metal is preferably Fe or Cu or a combination thereof.
[0077] In some illustrative embodiments, the second catalyst comprises a Cu and / or Fe promoted zeolite having an AEI, BEA, CHA, AFT, AFX, FAU, FER, KFI, MOR, MFI, MOR or MEL framework type, particularly a Cu and / or Fe promoted zeolite having a CHA and AEI framework as the molecular sieve component.
[0078] The promoter metal may be present in the metal-promoted molecular sieve in an amount of 0.1% to 20% by weight, 0.5% to 15% by weight, 1% to 10% by weight, or 2% to 6% by weight on an oxide basis, based on the total weight of the metal-promoted molecular sieve. In some illustrative embodiments where Cu or Fe is used as the promoter metal, the promoter metal is preferably present in an amount of 0.5% to 15% by weight, or 1% to 15% by weight, or 1% to 10% by weight on an oxide basis, based on the total weight of the metal-promoted molecular sieve.
[0079] The molecular sieve component may have an average crystallite size in the range of 0.1 to 4.0 micrometers (μm), or 0.5 to 1.5 μm.
[0080] When molecular sieves having an aluminosilicate framework are used, such as aluminosilicate zeolites and metal promoted aluminosilicate zeolites, the aluminosilicate framework preferably has a silica to alumina molar ratio (SAR) in the range of 2-200, 5-100, 8-50, or 10-30.
[0081] The second catalyst may optionally include additional components having SCR activity, such as a vanadium-based SCR catalyst containing a vanadium material on a refractory metal oxide support (such as alumina, silica, zirconia, titania, ceria and combinations thereof). Vanadium-based SCR catalysts are well known and widely used commercially in mobile exhaust treatment applications. For example, typical vanadium-based SCR catalyst compositions are described in U.S. Patent Nos. 4,010,238 and 4,085,193, the entire contents of which are incorporated herein by reference. Exemplary vanadium-based SCR catalyst compositions used commercially, especially in mobile applications, include 5% to 20% by weight of WO3 and 0.5% to 6% by weight of V2O5 supported on TiO2 particles. Those vanadium-based SCR catalysts may include additional inorganic materials, such as SiO2 and ZrO2.
[0082] <Coating structure>
[0083] In the catalytic article according to the present invention, the coating layer in the first coating structure or the second coating layer in the second coating structure respectively has inter-particle pores with a porosity of 5.7% or more, or 7.0% or more, preferably 8.0% or more, especially 9.0% or more. More preferably, the coating layer in the first coating structure or the second coating layer in the second coating structure has inter-particle pores with a porosity of 25% or less, preferably 20% or less, especially 15% or less.
[0084] In particular, the coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity ranging from 5.7% to 25%, or 7.0% to 20%, or 8.0% to 15%, or 9.0% to 15%.
[0085] In this context, interparticle pores refer in particular to pores having a pore size of less than 50 micrometers (μm), preferably in the range of 5 to 30 micrometers (μm), more preferably in the range of 8 to 20 μm as measured by scanning electron microscopy (SEM). The pore size of a pore refers to the diameter assuming that the pore shape is a perfect circle, as determined by SEM.
[0086] In some embodiments, the catalytic article according to the present invention has a first coating structure and includes a coating comprising a first catalyst containing a precious metal component and a second catalyst containing a molecular sieve component (hereinafter also referred to as "a coating comprising a first catalyst and a second catalyst"). In other words, the first catalyst and the second catalyst are not separated in different layers, but are physically mixed in a single coating.
[0087] In those embodiments in which the catalytic article according to the present invention has a first coating structure, the coating comprising the first catalyst and the second catalyst can be arranged along the gas flow channel over the entire axial length of the substrate, i.e., extending from the inlet end to the outlet end. Alternatively, the coating comprising the first catalyst and the second catalyst can extend along the gas flow channel from the outlet end toward the inlet end over a portion of the axial length of the substrate (e.g., 30% to less than 100%, including 40%, 50%, 60%, 70%, 80% or 90% of the length of the substrate). In the latter case, another coating (e.g., another SCR catalyst coating) can be arranged upstream, i.e., over a portion of the length of the substrate from the inlet end toward the outlet end.
[0088] The first catalyst and the second catalyst may be contained in the coating layer including the first catalyst and the second catalyst in a weight ratio ranging from 1:15 to 2:1, preferably from 1:10 to 1:1, and more preferably from 1:8 to 1:2.
[0089] In some other embodiments, the catalytic article according to the present invention has a second coating structure and includes i) a first coating layer comprising a first catalyst containing a precious metal component (hereinafter, also referred to as the "first coating layer") and ii) a second coating layer covering at least a portion of the first coating layer and comprising a second catalyst containing a molecular sieve component (hereinafter, also referred to as the "second coating layer").
[0090] In those embodiments where the catalytic article has a second coating structure, the second coating is directly on top of the first coating and may cover a portion or all of the first coating.
[0091] For example, in some specific embodiments, the catalytic article has a second coating structure and includes i) a first coating comprising a first catalyst containing a precious metal component and ii) a second coating comprising a second catalyst containing a molecular sieve component, wherein both the first and second coatings extend along the gas flow channel over the entire axial length of the substrate and the second coating is directly on top of the first coating.
[0092] In some other specific embodiments, the catalytic article has a second coating structure and includes i) a first coating comprising a first catalyst containing a precious metal component and ii) a second coating comprising a second catalyst containing a molecular sieve component, wherein the first coating extends along the gas flow channel over the entire axial length of the substrate, and the second coating is directly on top of the first coating and extends from the inlet end or the outlet end along the gas flow channel over a portion of the axial length of the substrate (e.g., 30% to less than 100%, including 40%, 50%, 60%, 70%, 80% or 90% of the length of the substrate).
[0093] In some additional specific embodiments, the catalytic article has a second coating structure and includes i) a first coating comprising a first catalyst containing a precious metal component and ii) a second coating comprising a second catalyst containing a molecular sieve component, wherein the first coating extends from the inlet end or the outlet end along the gas flow channel over a portion of the axial length of the substrate (e.g., 30% to less than 100%, including 40%, 50%, 60%, 70%, 80% or 90% of the length of the substrate), and the second coating extends directly on top of the first coating and along the gas flow channel over the entire axial length of the substrate.
[0094] In some further specific embodiments, the catalytic article has a second coating structure and includes i) a first coating comprising a first catalyst containing a precious metal component and ii) a second coating comprising a second catalyst containing a molecular sieve component, wherein the first coating and the second coating extend from the outlet end and the inlet end respectively along the gas flow channel over a partial axial length of the substrate (e.g., 30% to less than 100%, including 40%, 50%, 60%, 70%, 80% or 90% of the length of the substrate), and the second coating is directly on top of the first coating and overlaps with the first coating.
[0095] Optionally, the catalytic article having the second coating structure may further include a third coating adjacent to or overlapping the second coating. The third coating is, for example, another SCR catalyst coating different from the second coating, and may or may not have porosity as described herein.
[0096] Therefore, in certain specific embodiments, the catalytic article has a second coating structure and includes i) a first coating comprising a first catalyst comprising a precious metal component, ii) a second coating comprising a second catalyst comprising a molecular sieve component, and iii) a third SCR catalyst coating, wherein the first coating extends along the gas flow channel over the entire axial length of the substrate, and the second and third coatings are on top of the first coating and extend from opposite ends along the gas flow channel over a portion of the axial length of the substrate. For example, the second coating extends from the inlet end and the third coating extends from the outlet end, both extending along the gas flow channel over a portion of the axial length of the substrate.
[0097] In the above embodiment in which the catalytic article has a second coating structure, the first catalyst and the second catalyst may be contained in a weight ratio ranging from 1:15 to 2:1, preferably 1:10 to 1:1, more preferably 1:8 to 1:2.
[0098] It should be understood that a single sheet or more than one sheet of substrate may be present in the catalytic article having the second coating structure as described herein without any limitation. For example, the catalytic article as described in "some other specific embodiments" above may include two sheets of substrate, one of which carries a portion of the first coating and the second coating, and the other carries the remaining portion of the first coating.
[0099] Any possible variation including two or more sheets of substrate is contemplated and included in the present invention.
[0100] In any embodiment according to the present invention, the precious metal component may be present in an amount of 0.01 to 20 g / ft2 calculated as the corresponding precious metal based on the volume of the substrate. 3 , preferably 0.5 to 10 g / ft 3 , more preferably 1.5 to 5 g / ft 3 The total amount exists.
[0101] Additionally or alternatively, the molecular sieve component may be present in an amount of 0.5 to 6.0 g / in based on the volume of the substrate. 3 , preferably 1.0 to 4.0 g / in 3 , more preferably 1.5 to 3.0 g / in 3 The total amount exists.
[0102] Any coating as described herein may also contain one or more other components in addition to the catalyst. The other components may be non-catalytically active components, such as processing aids useful in the preparation of catalytic articles, such as stabilizers, surfactants and binders.
[0103] Other components may also be catalytically active. For example, when the catalytic article according to the present invention comprises a first coating and a second coating as described herein, the first coating may further comprise a zeolite or non-zeolite molecular sieve component. Suitable molecular sieves may be selected from those molecular sieve components as described for the second catalyst.
[0104] The catalytic article according to the invention can be prepared by conventional washcoating methods. Washcoating methods generally involve applying one or more slurries containing the corresponding catalyst to a substrate. For the purposes of the present invention, a pore former in the form of particles is used in one or more slurries for providing interparticle pores with the desired porosity in the obtained coating. The pore former is contained in the slurry from which a coating in a first coating structure or a second coating in a second coating structure with the desired porosity is obtained upon calcination.
[0105] Thus, in a second aspect, the present invention provides a method for preparing a catalytic article for treating an exhaust gas stream, the method comprising
[0106] - applying a slurry comprising a first catalyst comprising a precious metal component, a second catalyst comprising a molecular sieve component, and a pore former to a substrate, optionally drying, and calcining to form a coating in a first coating structure,
[0107] or
[0108] - applying a first slurry comprising a first catalyst containing a precious metal component to a substrate, and drying and / or calcining to form a first coating, and then applying a second slurry comprising a second catalyst containing a molecular sieve component and a pore former, optionally drying, and calcining to form a second coating in the first coating structure,
[0109] Therein, the pore former is in the form of particles and is used in an amount of at least 15% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0110] It is contemplated that the substrate used to carry the coating in the first coating structure or the first coating in the second coating structure may be a blank substrate or may have been coated with any suitable base coating. A blank substrate is intended to mean a substrate that does not carry a coating before the coating in the first coating structure or the first coating in the second coating structure is applied thereto.
[0111] The pore former is preferably used in an amount of at least 18% by weight or at least 20% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively. In particular, the pore former may be used in an amount of 50% by weight or less, or 40% by weight or less, based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0112] In particular, the pore former may be used in an amount of 18 to 50% by weight, or 20 to 40% by weight based on the loading of the coating layer in the first coating structure or the second coating layer in the second coating structure, respectively.
[0113] The pore forming agent can be an organic or inorganic material particle that can be burned off during the calcination step and leave a void to provide a coating. For example, the pore forming agent can be selected from organic materials such as natural and synthetic polymers, organic small molecule compounds, inorganic materials such as inorganic salts and carbon materials, natural materials containing cellulose, and any combination thereof.
[0114] Suitable natural and synthetic polymers as pore formers may include, but are not limited to, polyether polyols such as polyethylene glycol and its alkyl-terminated derivatives, styrene homopolymers or copolymers such as polystyrene, poly(meth)acrylic acid and its ester derivatives such as polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, and any combination thereof.
[0115] Suitable organic small molecule compounds as pore formers may include, but are not limited to, benzoic acid and its derivatives, urea (urea), sugar crystals, and any combination thereof.
[0116] Suitable inorganic salts as pore formers may include, but are not limited to, ammonium bicarbonate, magnesium carbonate, and any combination thereof.
[0117] Suitable carbon materials as pore formers may include, but are not limited to, carbon black, carbon fibers, graphite, and any combination thereof.
[0118] Suitable cellulose-containing natural materials as pore formers can be granular products from dried plants, including but not limited to sunflower, cotton, rice, wheat, sorghum, breadfruit, sugar cane, corn, bamboo and any combination thereof. Granular products can be obtained from different parts of plants, such as leaves, bark, stalks, roots, shells and any combination thereof.
[0119] The pore former can be particles having various geometric shapes, including but not limited to spheres, tablets, cylinders or fibers. Preferably, the pore former has an average particle size D in the range of 15 to 25 μm, preferably 17 to 21 μm. 50 .
[0120] The steps of preparing and applying the slurry, drying and calcining the coated slurry can all be carried out in the conventional manner for the wash coating method without any specific restrictions. Generally, the slurry for wash coating can be prepared by suspending the finely dispersed particles of the catalyst in an appropriate carrier (e.g., water), and a promoter, stabilizer and / or surfactant can be added to the slurry in the form of a solution in water or a carrier miscible with water. The slurry can be crushed / ground so that substantially all solids have an average particle size of less than 10 microns (e.g., in the range of 0.1 to 8 microns). Crushing / grinding can be completed in a ball mill, a continuous Eiger mill or other similar equipment. The suspension or slurry generally has a pH of 2 to less than 9, and if necessary, can be adjusted by adding an inorganic or organic acid or alkali. The solid content of the slurry can be, for example, 15% to 60% by weight. The obtained slurry can be applied to the substrate by dipping the substrate into the slurry, or otherwise applied to the substrate so that the catalyst coating of the desired load will be deposited on the substrate. Thereafter, the coated substrate may optionally be dried at a temperature in the range of 100° C. to 300° C. Calcination is typically performed by heating at a temperature in the range of 350° C. to 650° C. for a period of time, such as 1 to 3 hours. Drying and calcining are typically performed in air. If necessary, the coating, drying and calcining processes may be repeated to achieve the final desired weight amount of the coating on the support. The loading of the coating may be determined by calculating the weight difference before and after the coating is applied. When used, the pore former may be incorporated into the slurry at any time during the preparation of the slurry (e.g., after crushing / grinding).
[0121] The catalytic article according to the invention may be used to treat the exhaust gas stream from an automotive combustion engine, in particular a diesel engine.
[0122] Therefore, in a third aspect, the present invention relates to a system for treating an exhaust gas flow (especially originating from a diesel engine), the system comprising a source of reducing agent (e.g. NH3 or a precursor thereof) and a catalytic product as described in the first aspect above or as obtained according to the method as described in the second aspect above.
[0123] The system for treating the exhaust gas flow may further include one or more exhaust gas flow treatment elements. Conventional exhaust gas flow treatment elements include, but are not limited to, diesel oxidation catalysts (DOCs), selective catalytic reduction catalysts (SCRs), three-way conversion catalysts (TWCs), four-way conversion catalysts (FWCs), non-catalyzed or catalyzed soot filters (CSFs), NOx traps, hydrocarbon trap catalysts, sensors, and mixers.
[0124] In some embodiments, the system for treating the exhaust flow further comprises a diesel oxidation catalyst (DOC) and a selective catalytic reduction (SCR) catalyst located downstream of the engine and upstream of the catalytic product. Preferably, the system for treating the exhaust flow further comprises a diesel oxidation catalyst (DOC), a catalyzed soot filter (CSF), and a selective catalytic reduction (SCR) catalyst located upstream of the catalytic product.
[0125] In a fourth aspect, the invention relates to a method for treating an exhaust gas stream containing nitrogen oxides, the method comprising contacting the exhaust gas stream with a catalytic article as described in the first aspect or passing the exhaust gas stream through a system as described in the third aspect in the presence of NH3 as a reducing agent. The method is particularly useful for treating an exhaust gas stream originating from a diesel engine.
[0126] Example
[0127] Various embodiments are listed below. It will be understood that the embodiments listed below can be combined with all aspects of the scope of the present invention and other embodiments.
[0128] 1. A catalytic article for treating an exhaust gas stream, comprising
[0129] - substrate,
[0130] - a coating comprising a first catalyst comprising a noble metal component and a second catalyst comprising a molecular sieve component,
[0131] In the first coating structure;
[0132] or
[0133] - substrate,
[0134] - a first coating comprising a first catalyst comprising a precious metal component, and
[0135] - a second coating covering at least a portion of the first coating and comprising a second catalyst comprising a molecular sieve component,
[0136] In the second coating structure;
[0137] The coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 5.7% or more.
[0138] 2. The catalytic article of embodiment 1, wherein the molecular sieve is derived from an optionally metal-promoted zeolite.
[0139] 3. The catalytic article according to embodiment 1 or 2, wherein the molecular sieve component is selected from aluminosilicate zeolites having a framework type selected from the group consisting of AEI, AEL, AFI, AFT, AFO, AFX, AFR, ATO, BEA, CHA, DDR, EAB, EMT, ERI, EUO, FAU, FER, GME, HEU, JSR, KFI, LEV, LTA, LTL, LTN, MAZ, MEL, MFI, MOR, MOZ, MSO, MTW, MWW, OFF, RTH, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TON, TSC and WEN, preferably AEI, BEA, CHA, AFT, AFX, FAU, MOR, MFI, MOR and MEL, more preferably CHA and AEI.
[0140] 4. The catalytic article according to any of the preceding embodiments, wherein the molecular sieve component has an average crystallite size in the range of 0.1 to 4 microns.
[0141] 5. The catalytic article of embodiment 4, wherein the molecular sieve component has an average crystallite size in the range of 0.5 to 1.5 microns.
[0142] 6. The catalytic article according to any one of the preceding embodiments, wherein the coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 7.0% or more.
[0143] 7. The catalytic product according to embodiment 6, wherein the coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 8.0% or more.
[0144] 8. The catalytic article according to embodiment 7, wherein the coating in the first coating structure or the second coating in the second coating structure respectively has inter-particle pores with a porosity of 9.0% or more.
[0145] 9. The catalytic article according to any one of the preceding embodiments, wherein the coating in the first coating structure or the second coating in the second coating structure has inter-particle pores with a porosity of 25% or less.
[0146] 10. The catalytic article according to embodiment 9, wherein the coating layer in the first coating structure or the second coating layer in the second coating structure has inter-particle pores with a porosity of 20% or less.
[0147] 11. The catalytic article according to embodiment 10, wherein the coating in the first coating structure or the second coating in the second coating structure has inter-particle pores with a porosity of 15% or less.
[0148] 12. A catalytic product according to any one of the preceding embodiments, wherein the substrate has an inlet end and an outlet end defining its axial length and a plurality of thin parallel gas flow channels extending along the axial length, such as a flow-through substrate or a wall-flow substrate, preferably a flow-through substrate.
[0149] 13. The catalytic article of any preceding embodiment having a second coating structure, wherein the second coating is directly on top of the first coating and covers a portion or all of the first coating.
[0150] 14. The catalytic article according to embodiment 12, having the second coating structure, wherein both the first coating and the second coating extend along the gas flow channels over the entire axial length of the substrate.
[0151] 15. The catalytic article of embodiment 14, wherein the second coating is directly on top of the first coating.
[0152] 16. A method for preparing a catalytic article for treating an exhaust gas stream, the method comprising
[0153] - applying a slurry comprising a first catalyst comprising a precious metal component, a second catalyst comprising a molecular sieve component, and a pore former to a substrate, optionally drying, and calcining to form a coating in a first coating structure,
[0154] or
[0155] - applying a first slurry comprising a first catalyst containing a precious metal component to a substrate, and drying and / or calcining to form a first coating, and then applying a second slurry comprising a second catalyst containing a molecular sieve component and a pore former, optionally drying, and calcining to form a second coating in the first coating structure,
[0156] Therein, the pore former is in the form of particles and is used in an amount of at least 15% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0157] 17. The method of embodiment 16, wherein a catalytic article for treating an exhaust gas stream according to any one of embodiments 1 to 15 is prepared.
[0158] 18. The method of embodiment 16 or 17, wherein the pore former is used in an amount of at least 18% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0159] 19. The method of embodiment 18, wherein the pore former is used in an amount of at least 20% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0160] 20. The method of any one of embodiments 16 to 19, wherein the pore former is used in an amount of 50% or less by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0161] 21. The method of embodiment 20, wherein the pore former is used in an amount of 40% or less by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
[0162] 22. The method according to any one of embodiments 16 to 21, wherein the pore former is selected from organic materials such as natural and synthetic polymers, organic small molecule compounds, inorganic materials such as inorganic salts and carbon materials, natural materials containing cellulose, and any combination thereof.
[0163] 23. The method according to embodiment 22, wherein the pore former is selected from polyether polyols such as polyethylene glycol and its alkyl-terminated derivatives, styrene homopolymers or copolymers such as polystyrene, poly(meth)acrylic acid and its ester derivatives such as polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone and any combination thereof.
[0164] 24. The method according to any one of embodiments 16 to 23, wherein the pore former has an average particle size D in the range of 15 to 25 μm. 50 .
[0165] 25. The method according to embodiment 24, wherein the pore former has an average particle size D in the range of 17 to 21 μm. 50 .
[0166] 26. A system for treating an exhaust gas flow, the system comprising a reductant source (e.g., NH3 or a precursor thereof), a catalytic product according to any one of the foregoing embodiments 1 to 10 or a catalytic product obtained by a method according to any one of embodiments 11 to 17, and optionally a diesel oxidation catalyst (DOC), a selective catalytic reduction catalyst (SCR), a three-way conversion catalyst (TWC), a four-way conversion catalyst (FWC), a non-catalyzed or catalyzed soot filter (CSF), a NOx trap, a hydrocarbon trap catalyst, a sensor, and a mixer. One or more.
[0167] 27. A system according to embodiment 26, wherein the exhaust gas flow originates from an internal combustion engine, in particular a diesel engine.
[0168] 28. A method for treating an exhaust gas flow containing nitrogen oxides, the method comprising contacting the exhaust gas flow with a catalytic product according to any one of the foregoing embodiments 1 to 15 or a catalytic product obtained by the method according to any one of embodiments 16 to 25, or passing the exhaust gas flow through a system defined according to embodiment 26 or 27 in the presence of NH3 as a reducing agent.
[0169] The invention will be further illustrated by the following examples, which set forth particularly advantageous embodiments.While the examples are provided to illustrate the invention, they are not intended to limit the invention.
[0170] Examples
[0171] Comparative Example 1
[0172] Preparation of AMOx slurry
[0173] 4.5 g of an aqueous solution of tetraammine platinum (II) hydroxide (H14N4O2Pt, 12.6% Pt) was diluted into water and then loaded onto 250 g of an Al2O3-SiO2 composite oxide powder support (98.5 wt% Al2O3 and 1.5 wt% SiO2) by incipient wetness impregnation under constant stirring to ensure uniform distribution, thereby providing a slurry having a solid content of 42 wt%. Thereafter, the slurry was adjusted to a pH of about 4.0 and then ground to D 90 The particle size was 7 μm as measured with a Sympatec particle size analyzer.
[0174] Preparation of SCR slurry containing Cu-CHA
[0175] 78.7 g of aqueous zirconium acetate binder having a solid content of 30.0 wt% (calculated as ZrO2) was added dropwise to 160 g of DI water under stirring. After thorough mixing, 510.7 g of Cu-CHA powder having a solid content of 88.6 wt%, a Cu content of 5.0% (calculated as CuO based on the solid content) and a SAR (SiO2 / Al2O3 ratio) of 17 was slowly added under stirring at 400 rpm for 12 hours, and the obtained slurry was ground to a particle size of D 90 6 μm, as measured with a Sympatec particle size analyzer. 79.3 g of alumina sol with a solid content of 30 wt% was then added under stirring at 400 rpm. Before coating, the final solid content was adjusted to 37 wt% with DI H2O.
[0176] Applying the coating to the substrate
[0177] The AMOx coating was first applied to a ceramic flow-through monolithic core (1" x 3", 600 cpsi / 3 mil) as a substrate by immersing the core in the AMOx slurry. Excess slurry was carefully blown out using compressed air, followed by brief drying in flowing air at 250°C, and then calcined in a muffle furnace at 550°C (ramp 4°C / min) for 1 hour. After cooling to 250°C, the coated substrate was weighed to determine the AMOx catalyst loading. The loading of the AMOx coating was 0.5 g / in 3 (30 g / L), and the Pt loading was 2.0 g / ft 3 Thereafter, an SCR coating was applied using the same method as described above for the AMOx coating, with the SCR coating loading being 2.2 g / in 3 (135 g / L), and the Cu-CHA loading was 2.0 g / in 3 .
[0178] Comparative Example 2
[0179] The method described in Comparative Example 1 was repeated, except that the SCR slurry containing Cu-CHA further contained 25.0 g of polymethyl methacrylate (PMMA, SUNPMMA-S200 from SUNJIN Chemical), wherein D 50 = 19 μm, as measured with a Sympatec particle size analyzer, was added to the SCR slurry and stirred uniformly after the addition of the alumina sol was completed.
[0180] Comparative Example 3
[0181] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 50.0 g of polymethyl methacrylate (PMMA).
[0182] Comparative Example 4
[0183] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 65.0 g of polymethyl methacrylate (PMMA).
[0184] Example 1
[0185] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 100.0 g of polymethyl methacrylate (PMMA).
[0186] Example 2
[0187] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 150.0 g of polymethyl methacrylate (PMMA).
[0188] Example 3
[0189] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 200.0 g of polymethyl methacrylate (PMMA).
[0190] Example 4
[0191] The method described in Comparative Example 2 was repeated except that the SCR slurry containing Cu-CHA contained 250.0 g of polymethyl methacrylate (PMMA).
[0192] Comparative Example 5
[0193] The method described in Comparative Example 1 was repeated, except that 461.9Cu-AEI powder having a solid content of 98.0 wt%, a Cu content of 5.0% (calculated as CuO based on the solid content) and a SAR (SiO2 / Al2O3 ratio) of 16 was used instead of the Cu-CHA powder.
[0194] Example 5
[0195] The method as described in Comparative Example 5 was repeated, except that the SCR slurry containing Cu-AEI further contained 100.0 g of polymethyl methacrylate (PMMA), which was added to the SCR slurry and uniformly stirred after the addition of the alumina sol was completed.
[0196] Porosity measurement
[0197] The porosity of each fresh sample obtained from the above examples and comparative examples was measured by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / DES, Supra 55 from Zeiss). Photos were taken from a cross section of the substrate perpendicular to the axial direction of the substrate to determine the total cross-sectional area of the SCR coating and the total cross-sectional area of the pores in the SCR coating. The porosity was calculated according to
[0198] Porosity = (Ap / Ac) × 100%
[0199] in
[0200] Ap is the total cross-sectional area of the pores in the SCR coating, and
[0201] Ac is the total cross-sectional area of the SCR coating.
[0202] The total cross-sectional area of the pores can be determined by measuring the area of each pore cross section (as automatically observed from a photograph of the cross section by SEM / DES) and summing. In addition, the total cross-sectional area of the SCR coating can be determined in the same manner. The average of the measurements on the three photographs is reported as the porosity result.
[0203] Performance Testing
[0204] All catalytic performance tests were conducted on a flow reactor using simulated diesel exhaust having the composition shown below as feed gas for aged samples prepared from fresh samples from the above Examples and Comparative Examples by aging at 650° C. in 10 vol% water / air for 50 hours. Prior to testing, the aged samples were pretreated at 550° C. in N2 for 0.5 hours and cooled to 250° C.
[0205] Feed gas: 500 ppm NH3 in 10% O2, 8% CO2, 7% H2O and balance N2 at a space velocity of 100,000 h -1 .
[0206] The feed gas was blown into the reactor until a steady state of NH3 evolution was reached, and then the amount of NH3 evolution ([NH3]out) was recorded to calculate the NH3 conversion according to the following equation:
[0207] Conversion rate NH3 =([NH3] 进 -[NH3] 出 ) / [NH3] 进 ×100%.
[0208] Table 1
[0209]
[0210] As shown in the above table, the catalytic articles according to the present invention show improved NH3 conversion compared to conventional catalytic articles without pores (Examples 1 to 4 versus Comparative Example 1, Example 5 versus Comparative Example 5).
[0211] The inventors also unexpectedly discovered that the performance of the catalytic article is not mathematically proportional to the porosity. In other words, as the porosity increases, the catalytic article does not necessarily perform better. It can be seen that the catalytic articles with a porosity of 5% and 13% even show lower NH3 conversion than the conventional catalytic article with a porosity of zero (Comparative Examples 2 and 4 vs. Comparative Example 3), although the catalytic article with a porosity of 10% performs better than the conventional catalytic article with a porosity of zero.
Claims
1. A catalytic article for treating an exhaust gas stream, comprising - substrate, - a coating comprising a first catalyst comprising a noble metal component and a second catalyst comprising a molecular sieve component, In the first coating structure; or - substrate, - a first coating comprising a first catalyst comprising a precious metal component, and - a second coating covering at least a portion of the first coating and comprising a second catalyst comprising a molecular sieve component, In the second coating structure; in, The coating layer in the first coating structure or the second coating layer in the second coating structure respectively has inter-particle pores having a porosity of 5.7% or more.
2. The catalytic product according to claim 1, wherein The molecular sieve is selected from zeolites which are optionally metal promoted.
3. The catalytic product according to claim 1 or 2, wherein: The molecular sieve component is selected from aluminosilicate zeolites having a framework type selected from the group consisting of AEI, AEL, AFI, AFT, AFO, AFX, AFR, ATO, BEA, CHA, DDR, EAB, EMT, ERI, EUO, FAU, FER, GME, HEU, JSR, KFI, LEV, LTA, LTL, LTN, MAZ, MEL, MFI, MOR, MOZ, MSO, MTW, MWW, OFF, RTH, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TON, TSC and WEN, preferably AEI, BEA, CHA, AFT, AFX, FAU, MOR, MFI, MOR and MEL, more preferably CHA and AEI.
4. The catalytic article according to any one of the preceding claims, wherein: The molecular sieve component has an average crystallite size in the range of 0.1 to 4 microns or 0.5 to 1.5 microns.
5. The catalytic article according to any one of the preceding claims, wherein: The coating layer in the first coating structure or the second coating layer in the second coating structure respectively has inter-particle pores having a porosity of 7.0% or more, preferably 8.0% or more, and particularly 9.0% or more.
6. The catalytic article according to any one of the preceding claims, wherein: The coating layer in the first coating structure or the second coating layer in the second coating structure has inter-particle pores having a porosity of 25% or less, preferably 20% or less, particularly 15% or less.
7. The catalytic article according to any one of the preceding claims, wherein: The substrate has an inlet end and an outlet end defining its axial length and a plurality of thin parallel gas flow channels extending along the axial length, such as a flow-through substrate or a wall-flow substrate, preferably a flow-through substrate.
8. The catalytic article according to any one of the preceding claims, having the second coating structure, wherein: The second coating is directly on top of the first coating and covers a portion or all of the first coating.
9. The catalytic article according to claim 7, having the second coating structure, wherein: Both the first coating and the second coating extend along the gas flow channels the full axial length of the substrate.
10. The catalytic article according to claim 9, wherein The second coating is directly on top of the first coating.
11. A method for preparing a catalytic article for treating an exhaust gas stream, the method comprising - applying a slurry comprising a first catalyst comprising a precious metal component, a second catalyst comprising a molecular sieve component, and a pore former to a substrate, optionally drying, and calcining to form a coating in a first coating structure, or - applying a first slurry comprising a first catalyst containing a precious metal component to a substrate, and drying and / or calcining to form a first coating, and then applying a second slurry comprising a second catalyst containing a molecular sieve component and a pore former, optionally drying, and calcining to form a second coating in the first coating structure, in, The pore former is in the form of particles and is used in an amount of at least 15% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
12. The method according to claim 11, wherein: A catalytic article for treating an exhaust gas stream according to any one of claims 1 to 10 is prepared.
13. The method according to claim 11 or 12, wherein: The pore former is used in an amount of at least 18% by weight or at least 20% by weight based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
14. The method according to any one of claims 11 to 13, wherein: The pore former is used in an amount of 50% by weight or less, or 40% by weight or less, based on the loading of the coating in the first coating structure or the second coating in the second coating structure, respectively.
15. The method according to any one of claims 11 to 14, wherein: The pore former is selected from organic materials such as natural and synthetic polymers, organic small molecule compounds, inorganic materials such as inorganic salts and carbon materials, natural materials containing cellulose, and any combination thereof.
16. The method according to claim 15, wherein: The pore former is selected from polyether polyols such as polyethylene glycol and alkyl-terminated derivatives thereof, styrene homopolymers or copolymers such as polystyrene, poly(meth)acrylic acid and its ester derivatives such as polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone and any combination thereof.
17. The method according to any one of claims 11 to 16, wherein: The pore former has an average particle size D in the range of 15 to 25 μm, preferably 17 to 21 μm. 50 .
18. A system for treating an exhaust gas flow, the system comprising a source of reductant (e.g., NH3 or a precursor thereof), a catalytic product according to any one of the preceding claims 1 to 10 or a catalytic product obtained by a method according to any one of claims 11 to 17, and optionally one or more of a diesel oxidation catalyst (DOC), a selective catalytic reduction catalyst (SCR), a three-way conversion catalyst (TWC), a four-way conversion catalyst (FWC), a non-catalyzed or catalyzed soot filter (CSF), a NOx trap, a hydrocarbon trap catalyst, a sensor and a mixer.
19. The system of claim 18, wherein: The exhaust gas flow originates from an internal combustion engine, in particular a diesel engine.
20. A method for treating an exhaust gas stream containing nitrogen oxides, the method comprising contacting the exhaust gas stream with a catalytic product according to any one of the preceding claims 1 to 10 or a catalytic product obtained by a method according to any one of claims 11 to 17, or passing the exhaust gas stream through a system as defined in claim 18 or 19 in the presence of NH3 as a reducing agent.
Citation Information
Patent Citations
Ammonia slip catalyst with in-situ pt fixing
US20210299643A1
Proces for selective removal of nitrogen oxides from waste gases
US4010238A
Catalytic process for reducing nitrogen oxides to nitrogen
US4085193A
Integrated SCR and AMOX catalyst systems
WO2010062730A2
Integrated SCR and ammonia oxidation catalyst systems
WO2017037006A1
Cited By
Engine NH3 by-product purification catalyst based on equivalent combustion technology
CN121588884A